Kanong Application Based on Applied Ethnomusicology as Early Childhood Learning Media in the Industrial era 5.0 - Irawati, Eli; Wijayanto, Ary (Institut Seni Indonesia Padangpanjang, 2024)
Limited learning resources in the early childhood environment in arts and culture learning have an impact on the meta-emotional quality which includes cognitive, social emotional and language aspects of students, especially on knowledge of Indonesian musical instruments. Based on these problems, this research aims to implement the Kanong application based on applied ethnomusicology as an effort to increase cognitive and social emotional, language competence. This research uses the emotion regulation theory proposed by Oschner and Gross. The research method was preceded by ethnography to determine and find socio-cultural indicators that underlie the problem, then continued with a quasi experiment, namely using a sample of 30 students from groups A and B. The results of the research show that the limited learning resources in the early childhood education environment are caused by several factors, namely the lack of optimal meta-emotions in the form of awareness of emotional evolution in the form of human resource competency responses to technological developments, curriculum design that does not yet reflect emotional regulation, while the experimental results show that the application Kanong based on applied ethnomusicology is a solution in increasing students' awareness and meta-emotional abilities which include cognitive, social emotional